Short-wave solar radiation level willingly tolerated by lactating Holstein cows in an equatorial semi-arid environment - Octavio Oliveira, Steffan Edward [UNESP]; Melo Costa, Cintia Carol de [UNESP]; Freire de Souza, Joao Batista; Araujo Fernandes de Queiroz, Joao Paulo; Campos Maia, Alex Sandro [UNESP]; Macedo Costa, Leonardo Lelis de (Springer, 2014)
The amount of short-wave solar radiation willingly tolerated by lactating Holstein cows on pasture was determined in an equatorial semi-arid environment. The study was carried out on a dairy farm located in Limoeiro do Norte, CE, northeastern Brazil. The observed behaviours were as follows: grazing, under the sun, under the shade, standing, lying, ruminating, idling and wallowing in the water. The behaviours were recorded using instantaneous scan sampling at regular intervals of 15 min from 0600 to 1800 hours over 5 days. On all sampling days, the meteorological variables, including local short-wave solar radiation (R (S-W), W m(-2)), were recorded. The R (S-W) data were divided into five levels. The sun exposure was more frequent under low (100 %) and moderately low (97 %) levels, when R (S-W) remained below 500 W m(-2). The grazing was more intense under low (100 %) and moderately low (93 %) levels. Above 500 W m(-2), the grazing time significantly decreased (11 %). The cows avoided grazing under high (0 %) and very high (0 %) levels, when R (S-W) exceeded 700 W m(-2). The ruminating behaviour was more frequent under high (33 %) and very high (37 %) levels, in which the highest averages of R (S-W) were recorded (815 and 958 W m(-2), respectively). The standing posture was more frequent under low (100 %) and moderately low (97 %) levels. Therefore, the critical R (S-W) level that motivates cows to stop grazing and seek shade was in the interval between 500 and 700 W m(-2).
Keywords: Behaviour; Holstein cow; Semi-arid; Solar radiation